2010
DOI: 10.1002/wrna.69
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Puf proteins in mRNA degradation and translation

Abstract: Puf proteins are regulators of diverse eukaryotic processes including stem cell maintenance, organelle biogenesis, oogenesis, neuron function, and memory formation. At the molecular level, Puf proteins promote translational repression and/or degradation of target mRNAs by first interacting with conserved cis-elements in the 3' untranslated region (UTR). Once bound to an mRNA, Puf proteins elicit RNA repression by complex interactions with protein cofactors and regulatory machinery involved in translation and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
149
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(155 citation statements)
references
References 124 publications
(372 reference statements)
5
149
0
1
Order By: Relevance
“…The P values were evaluated via one-way ANOVAs. , presynaptic CS+US signals (blue), but not CS alone or US alone (gray), an CREB-independent mechanism relieves the translational block of RNA granules, which involves (i) STAUFEN detachment (38,41), (ii) FMR and PUMILIO dephosphorylations (38,42,43), and (iii) ORB phosphorylation by activated CaMKII, leading to the poly-A tail elongation (4)(5)(6). Consequently, these events recruit additional ribosomes to up-regulate mRNA translation of LTM-related proteins (42), which eventually lead to an enhanced response to the CS+.…”
Section: Methodsmentioning
confidence: 99%
“…The P values were evaluated via one-way ANOVAs. , presynaptic CS+US signals (blue), but not CS alone or US alone (gray), an CREB-independent mechanism relieves the translational block of RNA granules, which involves (i) STAUFEN detachment (38,41), (ii) FMR and PUMILIO dephosphorylations (38,42,43), and (iii) ORB phosphorylation by activated CaMKII, leading to the poly-A tail elongation (4)(5)(6). Consequently, these events recruit additional ribosomes to up-regulate mRNA translation of LTM-related proteins (42), which eventually lead to an enhanced response to the CS+.…”
Section: Methodsmentioning
confidence: 99%
“…Subtle degeneracy was observed at nucleotide position 4 in the sequences of APUM2 and APUM6, whereas a higher degree of degeneracy was observed at position 5 in these sequences. Degeneracy at position 5 is common for many other PUF protein targets (23). APUM12 deviated from the classical one repeat-one nucleotide pattern for PUF binding, because it showed an insertion of an additional uracil near the 3Ј end of its consensus sequence when compared with the target sequences A Unique PUF RNA Target Sequence DECEMBER 11, 2015 • VOLUME 290 • NUMBER 50…”
Section: Prediction Of Puf Repeats In the Selected Apum Proteins-mentioning
confidence: 99%
“…PUF proteins repress target mRNA expression by inhibiting translation and/or inducing mRNA degradation (Miller and Olivas 2011), but the mechanisms and cofactors involved remain to be fully elucidated. Our recent results revealed that human and Drosophila PUFs possess multiple domains that contribute to repression .…”
Section: Introductionmentioning
confidence: 99%